Genetic variation patterns of β-thalassemia in Western Andalusia (Spain) reveal a structure of specific mutations within the Iberian Peninsula - Luis J. Sánchez-Martínez; Candela L. Hernández; Juan N. Rodríguez; Jean M. Dugoujon; Andrea Novelletto; Paloma Ropero; Luisa Pereira; Rosario Calderón (Taylor & Francis Group, 2021)
Background Analyses of the genomic variation in the western Mediterranean population are being used to reveal its evolutionary history and to understand the molecular basis of particular diseases. Aim To observe the β-thalassemia mutational spectrum in western Andalusia, Spain, in the context of the Mediterranean. In addition, associations between disease and neutral gene variants within the β-globin gene (HBB) were also evaluated. Subjects and methods This study included 63 unrelated individuals diagnosed with β-thalassemia. In addition, 97 unrelated, healthy subjects of the same territory were also analysed as proxies of the normal genetic background. Allele associations and population genetic structure analyses were performed using different methodologies. Results Data have revealed a rather restricted spectrum of β-thalassemia mutations in the analysed sample. Although the detected variants fit well with the Mediterranean pattern, certain singularities support a structure of some specific β-thalassemia alleles. The IVSI-1 (G > A) shows a strong regionalisation. The spatial correlogram revealed a typically narrow wave structure, presumably linked to genetic isolation and genetic drift. Conclusions The long history of endemic malaria in the study territory, the rather high consanguinity rates among its autochthonous population, and other demographic features have been used here to understand the western Andalusian β-thalassemia molecular portrait.